Synthesis and characterization of a Sr0.95Y0.05TiO3−δ-based hydrogen electrode for reversible solid oxide cells. Issue 22 (9th February 2015) - Ling, Yihan; Chen, Luyang; Lin, Bin; Yu, Weili; Isimjan, Tayirjan T.; Zhao, Ling; Liu, Xingqin
Abstract : Reversible solid oxide cells (RSOCs) can generate electricity as solid oxide fuel cells (SOFC) facing a shortage of electricity and can also store the electricity as solid oxide electrolysis cells (SOEC) at the time of excessive electricity. Abstract : Reversible solid oxide cells (RSOCs) can generate electricity as solid oxide fuel cells (SOFC) facing a shortage of electricity and can also store the electricity as solid oxide electrolysis cells (SOEC) at the time of excessive electricity. The composite Sr0.95 Y0.05 TiO3− δ –Sm0.2 Ce0.8 O1.9 (SYT–SDC) as the hydrogen electrode provides a promising alternative for a conventional Ni/YSZ. The possible charge compensation mechanism of SYT is described as Sr0.95 Y0.05 Ti0.95−2 δ 4+ Ti2 δ +0.05 3+ O3− δ . The Ti 3+ is approximately 11.73% in the reduced SYT by XRD Rietveld refinement, electron paramagnetic resonance (EPR) and thermogravimetry (TG) analysis. Voltage–current curves and impedance spectra are measured as a function of applied voltages to characterize the cells. The bulk resistance ( R o ) and the electrode polarization resistance ( R p ) at open circuit voltages (OCV) at 750 °C are 9.06 Ω cm 2 and 10.57 Ω cm 2, respectively. The R o values have a small amount of changes with small slopes both in the SOFC (−0.29 Ω cm 2 V −1 ) and SOEC mode (0.5 Ω cm 2 V −1 ), whereas the R p values decrease all the time with the increasing voltages at both the SOFC (−2.59 Ω cm 2 V −1 ) and SOEC mode (−9.65 Ω cm 2 V −1 ), indicating that the electrical conductivity and electro-catalytic property of the SYT-based hydrogen electrode can be improved under the SOEC mode.